O efeito das adições de Y na microestrutura, comportamento mecânico e resistência à corrosão da liga Ti-35Nb para aplicações biomédicas - Matos, Gusttavo Reis Leite (2022)
β-type titanium alloys are the most suitable for the manufacture of implants for the orthopedic and dental sector, a reason attributed to the commonly added alloy elements that make it possible to obtain more optimized properties. The Ti-Nb system has received attention for presenting lower elastic modulus values, in addition to high corrosion resistance and greater biocompatibility, due to the formation of more protective and stable oxides that allow minimal release of metal ions in body fluids. However, its mechanical properties still need improvement and, in this sense, strengthening by oxide dispersion is considered a way to improve the mechanical behavior without affecting the modulus of elasticity. Yttrium (Y) additions have been considered, given the tendency to form oxide particles in the alloy melting step, in addition to its biocompatible nature. In this study, new Ti-35Nb-xY alloys, obtained by arc melting, were heat treated and cooled in water. The results showed that Y additions did not affect the formation of the α” martensitic phase and that Y2O3 particles are present in the microstructure and provided grain refinement. On the other hand, the sizes and distribution of Y2O3 particles had deleterious effects on mechanical strength and did not contribute to the increase in hardness. However, the additions of Y increased the corrosion resistance of the Ti-35Nb alloy in SBF medium.